Study on the origin and nature of the adenomatoid odontogenic tumor by immunohistochemistry - Crivelini, Marcelo Macedo [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Felipini, Renata Callestini [UNESP] (Journal Of Applied Oral Science : Revista Fob, 2005)
The adenomatoid odontogenic tumor (AOT) is a clinically benign lesion. Discussions about the AOT hamartomatous or neoplastic nature, and the probable odontogenic epithelial cell it originates from still exist. This research aimed to study and discuss the subject by the immunohistochemical detection of cytokeratins, laminin, collagen IV, PCNA and p53 in 8 tumor samples and 8 dental follicle samples containing reduced enamel epithelium. The results have shown that CK14 labelling indicated differentiation grades for secreting ameloblasts or ameloblasts in the post-secreting stage in the adenomatoid structure of AOT. Laminin, found on the luminal surface of adenomatoid structures, was compatible with the reduced enamel epithelium during the protective stage of amelogenesis. PCNA specifically labelled the spindled areas and peripheral cords of the AOT, indicating that these areas are responsible for tumor growth. After considerations about pathogenesis, the authors suggested that the nature of AOT is hamartomatous with histogenesis from the reduced enamel epithelium.

O tumor odontogênico adenomatóide (TOA) é uma lesão clinicamente benigna, cujas discussões acerca de sua natureza hamartomatosa ou neoplásica, e provável célula epitelial odontogênica de origem ainda existem. Este projeto de pesquisa teve por objetivo estudar o assunto através da detecção imuno-histoquímica das citoqueratinas, laminina, colágeno IV, PCNA e p53, utilizando-se para isso 08 amostras do tumor e 08 amostras de folículo pericoronário contendo epitélio reduzido do órgão do esmalte (EROE). Os resultados mostraram que a marcação da CK14 sinalizou graus de diferenciação para ameloblastos secretores ou pós-secretores nas estruturas adenomatóides do TOA, e a laminina presente em sua superfície luminal foi compatível com o EROE durante o "estágio protetor" da amelogênese. O PCNA marcou especificamente áreas enoveladas e cordões periféricos do TOA, indicando serem estes os responsáveis pelo seu crescimento. Após considerações sobre patogênese, os autores propuseram natureza hamartomatosa e histogênese a partir do EROE para o TOA.
Estudo da origem e natureza do tumor odontogênico adenomatóide pela imunoistoquímica
Keywords: Odontogenic neoplasms; Adenomatoid odontogenic tumor; Immunohistochemistry; Neoplasias odontogênicas; Tumor odontogênico adenomatóide; Imunoistoquímica